The spectrum of injuries resulting from posterior abdominal stab wounds: a South African experience - Kong, VY (Ann R Coll Surg Engl, 2015)
INTRODUCTION: The spectrum of injury associated with anterior abdominal stab wounds (SWs) is well established. The literature on the spectrum of organ injury associated with SWs to the posterior abdomen, however, is limited. METHODS: We reviewed our experience of 105 consecutive patients who had established indications for laparotomy managed over a 4-year period in a high volume trauma service in South Africa. RESULTS: Of the 105 patients, 97 (92%) were male and the overall mean age was 24 years. Fifty-seven patients (54%) had immediate indications for laparotomy. The remaining 48 patients (46%) initially underwent active clinical observation and the indications for laparotomy became apparent during the observation period. Of the 105 laparotomies performed, 94 (90%) were positive and 11 (10%) were negative. Of the 94 positive laparotomies, 92 were therapeutic and 2 were non-therapeutic. A total of 176 organ injuries were identified: 50 (53%) of the 94 patients sustained a single organ injury while the remaining 44 (47%) sustained multiple organ injuries. The most commonly injured organs were the colon (n=63), spleen (n=21) and kidney (n=19). CONCLUSIONS: The pattern of intra-abdominal injuries secondary to SWs to the posterior abdomen is different to that seen with the anterior abdomen. Colonic injury is most commonly encountered, followed by injuries to the spleen and kidney. Clinicians must remain vigilant because of the potential for occult injuries.